KOMPONEN HASIL DAN MUTU BIJI BEBERAPA VARIETAS TANAMAN KEDELAI (Glycinemax (L.) Merril) YANG DITANAM PADA EMPAT WAKTU APLIKASI PUPUK NITROGEN - Dessy Natalina Pandiangan; Aslim Rasyad2 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Since grain soybean is high in protein content, nitrogen addition may be required at the time of pod development and grain filing. This research was conducted to identify the appropriate time of N application during soybean growth. The field experiment was established at experimental farm of the Faculty of Agriculture, Riau University, inPekanbaru, from JunetoOctober 2016. Three soybean genotypes; ie, Grobogan, Argomulyo and Kaba were planted under some timing of N applications; ie, no N applied, 25 kg kg N applied at planting, 25 kg N applied at 30 days after planting (DAP), and 25 kg N applied at planting added at the same rate at 30 DAP. The experiment was assigned in a randomized block design with 3 replications. Parametersmeasured were filled pod numbersperplant, seeds numberperplant, seed weightperplant, grain yieldm-2, 100-seed weight, oil contents and protein contents of the seed. The results showedthat the application of Nitrogen fertilizer affected yield component and grain quality ofGrobogan, Argomulyo and Kaba. Application of 25 kg N per haat planting date and added at the same rate at flowering stageresulted higher number of filled pod, grain weight per plant, grain yield per m2 and grain protein content than otherapplication timings.Keywords: Yield Potential and Grain Quality, Time ApplicationofNitrogen Fertilizer, SoybeanVarieties